Revolutionizing chronic endometritis diagnosis: real-time polymerase chain reaction unveils microbial pathogens in Indian women with abnormal bleeding and reproductive challengesAJOG Global Reports at a Glance - Murugan Nandagopal, M.Phil, Ph.D., PDF; Rajesh Rajan N, M.Sc; Chirayu Padhiar, MBBS., DCP; Mayur Abhaya, MS.; Uma Bansal, MS (OG); Prakash Ghambir, MD (Ped) (Elsevier, 2024)
Background: This study aimed to assess the utility of real-time-polymerase chain reaction (PCR) for diagnosing chronic endometritis (CE) by targeting 11 prevalent pathogens and to compare the outcomes with conventional culture-based diagnosis. Study Design: A retrospective analysis was conducted on 500 patients with clinical conditions such as abnormal bleeding, in vitro fertilization failure, recurrent implantation failure, recurrent miscarriage, and recurrent pregnancy loss. The prevalence of 11 key pathogens associated with CE was evaluated in endometrial biopsy samples. Results: In our study, PCR identified 318 cases (63.6%) positive for at least one of the 11 investigated pathogens, while culture-based methods detected 115 cases (23%). Predominant pathogens detected by PCR included Enterococcus faecalis (E. faecalis) (19%), Escherichia coli (E. coli) (6.8%), Staphylococcus aureus (S. aureus) (9%), Mycoplasma hominis (5%), Mycoplasma genitalium (6.2%), Streptococcus agalactiae (S. agalactiae) (4.2%), Ureaplasma urealyticum (4%), nontuberculous Mycobacterium (5.2%), Mycobacterium tuberculosis (1.2%), Neisseria gonorrhoeae (0.6%), and Chlamydia trachomatis (2.4%). Standard culture methods identified E. faecalis (10.8%), S. aureus (6.2%), E. coli (3.8%), and S. agalactiae (2.2%). Conclusion: The DICE panel proves itself as a swift, precise, and cost-effective diagnostic tool for detecting both culturable and nonculturable endometrial pathogens in CE. Demonstrating superiority, the Molecular method outshines microbial culture, ensuring accurate and sensitive detection of CE-associated pathogens, harmonizing seamlessly with histology and hysteroscopy findings.